Are FGFR and IDH1-2 alterations a positive prognostic factor in intrahepatic cholangiocarcinoma? An unresolved issue - Brandi, Giovanni; Deiana, Chiara; Galvani, Linda; Palloni, Andrea; Ricci, Angela Dalia; Rizzo, Alessandro; Tavolari, Simona (Frontiers in Oncology, 2023)
Despite representing some of the most common and investigated molecular changes in intrahepatic cholangiocarcinoma (iCCA), the prognostic role of FGFR and IDH1/2 alterations still remains an open question. In this review we provide a critical analysis of available literature data regarding this topic, underlining the strengths and pitfalls of each study reported. Despite the overall poor quality of current available studies, a general trend toward a better overall survival for FGFR2 rearrangements and, possibly, for FGFR2-3 alterations can be inferred. On the other hand, the positive prognostic role of IDH1/2 mutation seems much more uncertain. In this scenario, better designed clinical trials in these subsets of iCCA patients are needed in order to get definitive conclusions on this issue.